A new face of food security: A global perspective of the COVID-19 pandemic. (December 2022) - Saboori, Behnaz; Radmehr, Riza; Zhang, Yu Yvette; Zekri, Slim
Abstract: COVID-19 has impacted the world economy and food system in many aspects. We conducted a comprehensive examination of global food security during the COVID-19 pandemic by considering the food security index and its four key pillars (affordability, availability, quality and safety, and natural resources and resilience) for 102 countries. In addition to the fixed effect panel data estimator, the Method of Moments Quantile regression is useful for disaggregating the impact of the COVID-19 pandemic in relation to inflation, economic growth, urbanization, and agricultural land on global food security among countries with different levels of food security. We found that COVID-19 has negatively affected food security globally, especially in countries with a low food security level. The effect of income per capita and urbanization rate on the food security index is positive and statistically significant across all quantiles. Inflation rate and agricultural land, however, adversely affect food security, and this effect is stronger for countries with lower levels of food security. The results of affordability, availability, quality, and safety, and natural resources and resilience models provide meaningful implications for governments and policymakers to build resilience in food systems and to be better prepared for future crises and disruptions in the food supply. Highlights: This is a new perspective on global food security during the COVID-19 pandemic COVID-19 is more likely to negatively affect countries with lower levels of food security Food affordability and availability were more negatively affected in countries with high food security. COVID-19 affects food quality and safety differently in countries with low and high levels of food security. Natural resources and resilience were not affected by COVID-19